THE EFFECT OF PRUNING ON CHILI PEPPER STEMS (CAPSICUM FRUTESCENS L) ON PRODUCTIVITY - Irawan, Fery; Hanizar, Evi; Sugianto, Ferdy (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
This study aims to determine the effect of stem pruning on chili pepper plants (Capsicum frutescens L.) on plant height growth, number of productive branches, and fruit weight. The study was conducted using an experimental method with a randomized block design (RBD) consisting of two treatments, namely without pruning (control) and stem tip pruning, each with 21 sample plants. Data analysis was performed using the non-parametric Wilcoxon Signed Ranks Test. The results showed that stem pruning shortened the plants to an average of 69.14 cm, lower than the control at 132.91 cm, but was able to increase the number of productive branches to an average of 25.95 branches, much higher than the control at 5.86 branches. The average fruit weight of the treated plants was also greater, although not statistically significantly different.